Signal reconstruction of moving sound sources with a fixed microphone array. (1st March 2019) - Bi, Chuan-Xing; Li, Yong-Chang; Zhang, Yong-Bin; Zhang, Xiao-Zheng; Xu, Liang
Highlights: A time-wavenumber-domain method is proposed to eliminate the Doppler effect. Signals after eliminating the Doppler effect are used to reconstruct source signals. The proposed method can work stably at high speeds if increasing the array aperture. Abstract: The time-domain signals of noise sources are of great importance to acoustic design of machinery. One available way to obtain source signals is to reconstruct them from the acoustic signals measured by a microphone array. However, when sources are moving, the acoustic signals sampled by a fixed microphone array are distorted in amplitude and frequency due to the Doppler effect, leading to that the reconstructed source signals may not reflect the real information of sources. This paper first presents a time-wavenumber-domain method to eliminate the Doppler effect in the measured acoustic signals, in which no priori information on the number, frequencies and locations of sources is needed. Then the acoustic signals after eliminating the Doppler effect are used as the input of the passive time reversal method to reconstruct source signals. Numerical simulation and experimental results show that the proposed method can effectively eliminate the Doppler effect and accurately reconstruct the source signals even when the sources emit transient signals. It is also found that the proposed method can work stably when the sources are moving at high speeds if increasing the array aperture and in the situation of low signal-to-noise ratio.